FACTORS INFLUENCING INTENTION TO DONATE AT THE MOSQUES USING QRIS IN BANDA ACEH - Arifin, Muhammad; Meutia, Rachmi; Zakiiya, Ghulaman (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2025)
Charity is one form of generosity that plays an important role in helping those in need. With the advancement of technology, methods of collecting donations (Sadaqah) have also undergone transformation, one of which is through the use of QRIS (Quick Response Code Indonesian Standard). The use of QRIS in charity offers several advantages, such as convenience, transparency, efficiency, and security. Donors can make contributions quickly and practically by simply scanning a QR code using a digital payment application, without the need to carry cash or perform manual bank transfers. This study aims to examine the influence of financial literacy, perception of benefits and perception of ease on the interest in donating at mosques using QRIS among mosque congregants in Banda Aceh City (Study on Mesjid Raya Baiturrahman, Mesjid Oman Al-Makmur, and Mesjid Jamik Unsyiah). The research method used is quantitative with a multiple linear regression model. The primary data was obtained through questionnaires given to the congregants of these mosques. Partial test results show that these three variables; financial literacy, perception of benefits and perception of ease have positive influence on the interest in donating at the mosque using QRIS in Banda Aceh City. The findings offer insight that although QRIS can enhance mosque donations, it is crucial to address financial literacy and comprehension obstacles to optimize its efficacy for the donors.AbstrakSedekah merupakan salah satu bentuk kedermawanan yang memegang peranan penting dalam membantu mereka yang membutuhkan. Seiring dengan kemajuan teknologi, metode pengumpulan infak (sadaqah) pun mengalami transformasi, salah satunya melalui penggunaan QRIS (Quick Response Code Indonesian Standard). Penggunaan QRIS dalam bersedekah menawarkan beberapa keuntungan, seperti kemudahan, transparansi, efisiensi, dan keamanan. Para donatur dapat memberikan donasi secara cepat dan praktis hanya dengan memproses kode QR menggunakan aplikasi pembayaran digital, tanpa perlu membawa uang tunai atau melakukan transfer bank secara manual. Penelitian ini bertujuan untuk menguji pengaruh literasi keuangan, persepsi kemudahan, dan persepsi manfaat terhadap minat berdonasi di masjid menggunakan QRIS pada jamaah masjid di Kota Banda Aceh (Studi di Mesjid Raya Baiturrahman, Mesjid Oman Al-makmur, dan Mesjid Jamik Unyiah). Metode penelitian yang digunakan adalah kuantitatif dengan model regresi linier berganda. Hasil uji parsial menunjukkan bahwa ketiga variabel tersebut; Literasi keuangan, persepsi kemudahan, dan persepsi manfaat berpengaruh terhadap minat berdonasi di masjid menggunakan QRIS di Kota Banda Aceh. Hasil penelitian ini memberikan wawasan bahwa meskipun QRIS dapat meningkatkan donasi masjid, namun kendala literasi dan pemahaman keuangan perlu diatasi agar efektivitasnya dapat optimal bagi para donatur.